A darkness strange and lovely - Dennard, Susan (Dennard, Susan. Something strange and deadly trilogy., 2013)
"Eleanor Fitt flees to Europe to seek the help of the Spirit-Hunters after a villain from her past resurfaces, only to find that, in Paris, there's a new kind of evil lurking"--